Dynamic operations and pricing of electric unmanned aerial vehicle systems and power networks. (July 2018) - Zhang, Kaiqing; Lu, Liqun; Lei, Chao; Zhu, Hao; Ouyang, Yanfeng
Highlights: Joint operations of coupled electric aviation transportation and power systems. Network flow model for electric aircraft trips and en-route charging assignments. System-wide cost minimization via electricity pricing of the power system operator. Dual-decomposition-based algorithm to preserve privacy of market players. Model applicability and algorithm performance tested through numerical examples. Abstract: The emergence of electric unmanned aerial vehicle (E-UAV) technologies, albeit somewhat futuristic, is anticipated to pose similar challenges to the system operation as those of electric vehicles (EVs). Notably, the charging of EVs en-route at charging stations has been recognized as a significant type of flexible load for power systems, which often imposes non-negligible impacts on the power system operator's decisions on electricity prices. Meanwhile, the charging cost based on charging time and price is part of the trip cost for the users, which can affect the spatio-temporal assignment of E-UAV traffic to charging stations. This paper aims at investigating joint operations of coupled power and electric aviation transportation systems that are associated with en-route charging of E-UAVs in a centrally controlled and yet dynamic setting, i.e., with time-varying travel demand and power system base load. Dynamic E-UAV charging assignment is used as a tool to smooth the power system load. A joint pricing scheme is proposed and a cost minimization problem is formulated to achieve system optimality for such coupled systems. Numerical experiments are performed to test the proposed pricing scheme and demonstrate the benefits of the framework for joint operations.